Deskripsi Permasalahan Guru dalam Menerapkan Pembelajaran IPAS pada Kurikulum Merdeka Kelas V SDN 06 Pontianak Timur - Ma'unah, Ma'unah; Hairida, Hairida; Ghasya, Dyoty Auliya Vilda (Innovative: Journal Of Social Science Research, 2024)
This research is a descriptive qualitative study to describe the problems face by researchs in implementing IPAS learning in the curriculum merdeka of SDN 06 East Pontianak. Data collection was carried out using observation techniques, interviews and documentary studies. Observations were carried out in class V using the passive partipacipatory observation method. Informants were selected using a purposive method with certain considerations and objectives, namely class V teachers. The results of this research are that in the learning planning process teachers still have difficulty in determining interesting learning methods and models, which are varied, not boring and easy to apply with students. On implementation of teaching and learning activities, difficulties faced by teachers including time management, students who are not ready to learn and a culture of lazy reading among students, and teachers’ lack of experience in implementing curriculum merdeka.